ANALISIS PENDAPATAN NELAYAN TRADISIONAL DENGAN MENGGUNAKAN ALAT TANGKAP UDANG LIFT NETS (Ali) DI KECAMATAN ARONGAN LAMBALEK KABUPATEN ACEH BARAT - Teuku Amarullah; Syarifah Zuraidah; Era Marjisa; Uswatun Hasanah (Biotik, 2020)
Capture fisheries is a source of livelihood for fishermen. Fishers in Arongan Lambalek are still classified as traditional fishermen and still use simple fishing gear in their operations. One of the fishing gear used is Lift Nets (Ali) fishing gear to catch shrimp. This study aims to determine the income of traditional fishermen using Lift Nets (Ali) fishing gear in Arongan Lambalek District, West Aceh Regency. This research was conducted from June to July 2020. The data collection method was purposive sampling method with 20 respondents. The analyzes used total cost, total beneficiary, profit and RCR. The results showed that, the amount of catch of fishermen using Lift Nets (Ali) fishing gear in Arongan Lambalek District was 2.872 kg / month with an average of 144 kg / month / fisherman, the total cost of 20 fishermen was Rp. 24.540,278 with an average total cost of Rp.1.227,013 months / fisherman, the amount of revenue from 20 fishermen is Rp.73.235,000 / month with an average income of Rp. 3.661,750 months / fisherman and income from 20 fishermen is Rp.48.694.722 / month and the average income of fishermen is Rp.2.434.736 / month and the average RCR of Rp.2.98 months / fisherman, which means RCR> 1, then traditional fishing business using Lift Nets (Ali) fishing gear is feasible.